Ecology of the Big Cities of the Russian Empire in Late 19th - Early 20th Centuries - G. Y. Afanasyev (Научный диалог, 2017)
The emergence of the first environmental problems in large cities of the Russian Empire in the period of the industrial revolution and the beginning of industrialization in the late 19th - early 20th centuries is discussed. The research urgency is caused by interest in the historical genesis of one of modern global problems in a regional context, the lack of a comprehensive study of this problem in scientific historical literature. Special attention is paid to industrial and domestic pollution of water resources of Russian cities. The author proves that the largest city of Russia, Saint Petersburg, was one of the most polluted cities in Europe. Data submitted to the statistical nature of the archival documents note the dynamics of the increase in the share of industrial pollution on the example of water resources in the total volume of emissions. It is noted that the problem of addressing issues of water pollution and the redevelopment of urban space becomes relevant for urban agriculture, draws the attention of the scientific community and bodies of supervision and control and starts to go to the beginning of the century from the municipal to the national level.